Teaching and learning Chinese as a second or foreign language emerging trends - Sung, Ko-Yin, 1977- (Lexington Books, 2020)
"This edited collection, with a focus on Chinese as a second or foreign language acquisition, consists of research studies that address one of three emerging themes: information and communication technology (ICT), young learners, and Chinese-character teaching and learning"--